PENGABDIAN KEPADA MASYARAKAT MELALUI KULIAH KERJA MAHASISWA (KKM) DI DESA KARANGPAPAK: UPAYA MENINGKATKAN KETERAMPILAN MAHASISWA DAN PENGEMBANGAN UMKM LOKAL - Santi Legianti Sutandi (STISIP Widyapuri Mandiri Sukabumi, 2023)
Student Work Lecture (KKM) is a concrete manifestation of the duties of lecturers and students in carrying out the Tri Dharma of Higher Education, namely the aspect of service. Through community service activities in Karangpapak village, there is a synergy between universities and the community as a form of knowledge democracy. The purpose of this service is to provide opportunities for students to apply the knowledge they have learned on campus, as well as to improve social, communication and collaboration skills. KKM is also useful for helping the community in overcoming various problems they face, such as in the fields of education, health, economy, environment, and others. The service is carried out through activities: design training workshops, digital marketing seminars, local umkm development, and teaching KKM. The results of the service provide an illustration of rising enthusiasm and increasing public understanding, especially in the field of branding and developing SMEs using online media. Thus, KKM can be an effective and meaningful learning tool for students and the community.